Absence of Rejection in a Facial Allograft Recipient with a Positive Flow Crossmatch 24 Months after Induction with Rabbit Anti-Thymocyte Globulin and Anti-CD20 Monoclonal Antibody - Bruce E. Gelb; J. Rodrigo Diaz-Siso; Natalie M. Plana; Adam Jacoby; William J. Rifkin; Kimberly S. Khouri; Daniel J. Ceradini; Eduardo D. Rodriguez (Case Reports in Transplantation)
Background. Donor-specific antibodies (DSA) to human leukocyte antigen increase the risk of accelerated rejection and allograft damage and reduce the likelihood of successful transplantation. Patients with full-thickness facial burns may benefit from facial allotransplantation. However, they are at a high risk of developing DSA due to standard features of their acute care. Case Presentation. A 41-year-old male with severe disfigurement from facial burns consented to facial allotransplantation in 2014; panel reactive antibody score was 0%. In August of 2015, a suitable donor was found. Complement-dependent cytotoxicity crossmatch was negative; flow cytometry crossmatch was positive to donor B cells. An induction immunosuppression strategy consisting of rabbit antithymocyte globulin, rituximab, tacrolimus, mycophenolate mofetil (MMF), and methylprednisolone taper was designed. Total face, scalp, eyelid, ears, and skeletal subunit allotransplantation was performed without operative, immunological, or infectious complications. Maintenance immunosuppression consists of tacrolimus, MMF, and prednisone. As of posttransplant month 24, the patient has not developed acute rejection or metabolic or infectious complications. Conclusions. To our knowledge, this is the first report of targeted B cell agents used for induction immunosuppression in skin-containing vascularized composite tissue allotransplantation. A cautious approach is warranted, but early results are promising for reconstructive transplant candidates given the exceptionally high rate of acute rejection episodes, particularly in the first year, in this patient population.